Nanotechnology-Based Cisplatin Intracellular Delivery to Enhance Chemo-Sensitivity of Ovarian Cancer - Bortot B (Dove Medical Press, 2020)
Barbara Bortot, 1 Maurizio Mongiat, 2 Erica Valencic, 3 Simeone Dal Monego, 4 Danilo Licastro, 4 Matteo Crosera, 5 Gianpiero Adami, 5 Enrico Rampazzo, 6 Giuseppe Ricci, 7, 8 Federico Romano, 7 Giovanni Maria Severini, 1 Stefania Biffi 7 1Department of Medical Genetics, Institute for Maternal and Child Health, IRCCS Burlo Garofolo, Trieste, Italy; 2Department of Research and Diagnosis, Division of Molecular Oncology, Centro Di Riferimento Oncologico Di Aviano (CRO) IRCCS, Aviano, Italy; 3Department of Pediatrics, Institute for Maternal and Child Health, IRCCS Burlo Garofolo, Trieste, Italy; 4ARGO Open Lab Platform for Genome Sequencing, AREA Science Park, Trieste, Italy; 5Department of Chemical and Pharmaceutical Sciences, University of Trieste, Trieste, Italy; 6Department of Chemistry “G. Ciamician”, University of Bologna, Bologna, Italy; 7Department of Obstetrics and Gynecology, Institute for Maternal and Child Health, IRCCS Burlo Garofolo, Trieste, Italy; 8Department of Medicine, Surgery and Health Sciences, University of Trieste, Trieste, ItalyCorrespondence: Stefania Biffi Email stefania.biffi@burlo.trieste.itBackground: Platinum resistance is a major challenge in the management of ovarian cancer. Even low levels of acquired resistance at the cellular level lead to impaired response to cisplatin. In ovarian cancer intraperitoneal therapy, nanoparticle formulation can improve the cisplatin’s pharmacokinetics and safety profile.Purpose: This work aimed to investigate the chemo-sensitivity of ovarian cancer SKOV3 cells upon short-term (72h) single treatment of cisplatin and cisplatin-loaded biodegradable nanoparticles (Cis-NP). The aim was then to determine the therapeutic properties of Cis-NP in vivo using a SKOV3-luc cells’ xenograft model in mice.Methods: Cell cytotoxicity was assessed after the exposure of the cell culture to cisplatin or Cis-NP. The effect of treatments on EMT and CSC-like phenotype was studied by analyzing a panel of markers by flow cytometry. Intracellular platinum concentration was determined by inductively coupled plasma mass spectrometry (ICS-MS), and gene expression was evaluated by RNAseq analysis. The efficacy of intraperitoneal chemotherapy was evaluated in a SKOV3-luc cells’ xenograft model in mice, through a combination of bioluminescence imaging, histological, and immunohistochemical analyses.Results: We observed in vitro that short-term treatment of cisplatin has a critical role in determining the potential induction of chemoresistance, and a nanotechnology-based drug delivery system can modulate it. The RNAseq actg 3nalysis underlines a protective effect of nanoparticle system according to their ability to down-regulate several genes involved in chemoresistance, cell proliferation, and apoptosis. The highest intracellular platinum concentration obtained with Cis-NP treatment significantly improved the efficacy. Consistent with in vitro results, we found that Cis-NP treatment in vivo can significantly reduce tumor burden and aggressiveness compared to the free drug.Conclusion: Nanoparticle-mediated cisplatin delivery may serve as an intracellular depot impacting the cisplatin pharmacodynamic performance at cellular levels. These features may contribute to improving the drawbacks of conventional intraperitoneal therapy, and therefore will require further investigations in vivo.Keywords: cisplatin resistance, ovarian cancer, SKOV3, nanoparticle, epithelial-mesenchymal transition, Ca125, apoptosis